2020
DOI: 10.1080/16078454.2020.1852763
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus is effective in relapsed/refractory autoimmune cytopenias: results of a single-center retrospective study

Abstract: Background: The standard therapies for autoimmune cytopenias, including idiopathic thrombocytopenia (ITP), autoimmune hemolytic anemia (AIHA) and Evans syndrome (ES), are corticosteroids and intravenous immunoglobulin G. However, the recurrence rate is high. Method: Data from 80 patients with ITP, AIHA and ES who were refractory to corticosteroids/ relapsed and were treated with tacrolimus from January 2018 to January 2019 in Peking Union Medical Colleague Hospital were reviewed retrospectively. Results: There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Retrospective data from patients with ITP who were refractory to corticosteroids/ relapsed and treated with tacrolimus showed that the overall response rate was 63.6% and the complete response rate was 30.3%. 13 These findings indicated that tacrolimus might be a novel approach for ITP. However, the underlying mechanism is poorly defined and needs to be explored further.…”
Section: Abstract Adiponectin Complement Mesenchymal Stem Cells Nlrp3...mentioning
confidence: 95%
“…Retrospective data from patients with ITP who were refractory to corticosteroids/ relapsed and treated with tacrolimus showed that the overall response rate was 63.6% and the complete response rate was 30.3%. 13 These findings indicated that tacrolimus might be a novel approach for ITP. However, the underlying mechanism is poorly defined and needs to be explored further.…”
Section: Abstract Adiponectin Complement Mesenchymal Stem Cells Nlrp3...mentioning
confidence: 95%
“…The response criteria were defined as follows (8,10). A complete response (CR) was defined as a platelet count ≥100×10 9 /L and no bleeding.…”
Section: Response Criteriamentioning
confidence: 99%
“…analysis of platelet counts at baseline and after 4 weeks, 8 weeks, 12 weeks and 24 weeks of TAC treatment. Disease activity for pSS patients was assessed by the authors using the European SS Disease Activity Index (ESS-DAI) score (8).…”
Section: Clinical and Immunological Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus (a selective T‑cell activation inhibitor, “off label”) is reported in quite a few cases of ITP associated with mostly allogenic transplant recipients. A new retrospective single-center study on the effect of tacrolimus in relapsed or refractory ITP showed an overall response rate of 63.6% (>100 G/l: CR: 30.3%; >30 G/l: PR: 33.3%) [ 22 ].…”
Section: Second-line Treatmentmentioning
confidence: 99%